TRANSFORMASI TATA KELOLA KEUANGAN SYARIAH DALAM MEMPERKUAT PROFITABILITAS DAN FINANCIAL SUSTAINABILITY DI PESANTREN MUKHTAR SYAFAAT BLOKAGUNG - Nur Widyasari; Muhammad Sidiq Purnomo; Achmad Faizal Ababil (Jurnal Manajemen Pendidikan, 2026)
This study examines the transition of Islamic boarding schools (pesantren) from purely educational institutions to independent economic entities through the transformation of sharia financial governance. The urgency of this research is based on the financial sustainability challenges often faced by traditional Islamic educational institutions. The objective is to formulate an effective, accountable, and applicable sharia financial governance model to increase profitability and long-term financial sustainability at the Mukhtar Syafaat Islamic Boarding School in Blokagung. The research method used is descriptive qualitative with a case study approach. Data were collected comprehensively through in-depth interviews, direct field observations, and documentation studies, which were then analyzed interactively based on the pillars of Good Corporate Governance (GCG). The results show that the implementation of transparent and accountable management transformation successfully optimized business diversification across various sectors. This restructuring was able to cover up to 40% of the institution's total operational costs independently. In addition to creating macroeconomic independence for the Islamic boarding school, the developed business unit also functions strategically as a practical educational laboratory to improve financial literacy and the entrepreneurial spirit of the students.